Creating A Web-Based Online Flashcard for Korean Vocabulary Memorization - Marcia Juvanie Chang; Adhi Kusnadi (IJNMT (International Journal of New Media Technology), 2018)
The Korean language is one of the most enthused language these days, mainly caused by the Hallyu wave. In traditional language learning techniques, flashcards are often used to help memorize simple syllables. Nowadays, online flashcards are used as a replacement for the traditional flashcards, which are proven to be more effective in many ways. However, the lack of use of appropriate methods to learn a new language will result in slower learning process. Therefore, by implementing a suitable method such as the Leitner method to an online flashcard will improve the learning process. The Leitner method sets aside the questions that can be answered easily and allows users to focus on questions that cannot be recalled consistently by distributing a set of questions in five different sections. Every question that can be answered by the user is moved to the next compartment, where the question will be repeated after a specified period of time. System usability scale is used to measure the usability of the application. This application has been successfully designed and built using the Leitner method to give the user the suitable interval of time for learning with flashcards and achieved a system usability scale score of 82,5. Index Terms— Leitner, Online flashcard, Laravel, Korean language.